Being young and Muslim: new cultural politics in the global South and North - Ruiz Herrera, Linda Naitze; Bayat, Asef (Religion and global politics series, 2010)
"This is an excellent collection of essays on youth in a number of Muslim majority (and minority) societies in the context of globalization and modernity. A particular strength of this volume is its ability to highlight the multiple and contested roles of religion and personal faith in the fashioning of contemporary youthful Muslim identities. Such insights often challenge secular Western master narratives of modernity and suggest credible reconceptualizations of what it means to be young and modern in a broad swath of the world today."